The Influence Of Perceived Usefulness, Perceived Ease Of Use And Perceived Quality Mysantika On Purchase Intention At Hotel Santika Bengkulu - Wiryadhana, Denny (Journal of Marketing and Emerging Economics, 2024)
This research aims to examine whether there is an Influence of Perceived Usefulness, Perceived Ease of Use, and Perceived Quality on Purchase Intention in using the MySantika application by guests from the online segment at Hotel Santika Bengkulu. This is a quantitative study. Primary data were obtained from the questionnaire results from 100 respondents. The data used are numbers and calculated using statistical methods. The data were analyzed using Multiple Linear Regression Data Analysis Method and processed using the SPSS 25 program. Based on the hypothesis testing results, for Perceived Usefulness, t count was obtained as 7.543 > t table or 1.985, and the significance value was 0.00 < 0.05, so the Perceived Usefulness variable influences the Purchase Intention variable in using MySantika. Perceived Ease of Use had a t count result of 8.217 > t table 1.985, with significance of 0.00 < 0.05, showing that the Perceived Ease of Use variable influences the Purchase Intention variable in using MySantika. Perceived Quality had a t count result of 9.451 > ttable 1.985, with a significance value of 0.00 < 0.05, indicating that the Perceived Quality variable influences Purchase Intention in using MySantika. Based on the F Test, the F value was 38.627, F table was 2.698, and the significance was 0.00 < 0.05. This shows that Perceived Usefulness, Perceived Ease of Use, and Perceived Quality simultaneously influence Purchase Intention in using the MySantika application, with a coefficient of determination (R2) of 53.3%, and the remaining 46.7% is explained by other variables not included in this study.